2008
DOI: 10.1007/s11060-008-9745-8
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory survival analysis of anti-angiogenic therapy for recurrent malignant glioma

Abstract: Recent clinical trial results suggest that anti-angiogenic therapy may be effective against recurrent malignant glioma. Though these treatments prolong progression-free survival, the extent to which they prolong overall survival is unknown. We pooled data from 34 patients treated at a single institution on phase II clinical trials of bevacizumab and cediranib, and we compared these data to 18 patients treated on clinical trials of cytotoxic chemotherapies. In univariate and multivariate analyses, treatment gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 18 publications
1
83
0
1
Order By: Relevance
“…However, upon recurrence, tumors treated with antiangiogenic therapies display an increasingly invasive phenotype [11,17,[26][27][28]. Given this phenotypic alteration observed in human patients, tumor borders following treatment of GL261 gliomas with aflibercept were analyzed.…”
Section: Antiangiogenic Therapy Results In Both Proangiogenic and Promentioning
confidence: 99%
See 1 more Smart Citation
“…However, upon recurrence, tumors treated with antiangiogenic therapies display an increasingly invasive phenotype [11,17,[26][27][28]. Given this phenotypic alteration observed in human patients, tumor borders following treatment of GL261 gliomas with aflibercept were analyzed.…”
Section: Antiangiogenic Therapy Results In Both Proangiogenic and Promentioning
confidence: 99%
“…While bevacizumab is the first antiangiogenic therapy approved for the treatment of recurrent GBM, results in clinical trials have been mixed [10]. Phase II clinical trials utilizing bevacizumab for the treatment of recurrent gliomas have demonstrated marked improvements in progression-free survival, although overall survival is only marginally, if at all, affected [11][12][13]. A more recent phase II trial investigating the effects of bevacizumab on recurrent anaplastic gliomas reported improvement in disease symptoms and increased tumor responsiveness, despite seeing no significant change in progression-free survival or overall survival [14].…”
Section: Introductionmentioning
confidence: 99%
“…The makeup of the current as well as novel revised response criteria do not allow to easily differentiate this effect on the barrier permeability from a direct antitumor effect [9,10]. So far, the unprecedented high response rates these agents produced in recurrent glioblastoma have not translated into a survival benefit of the same magnitude [11].…”
Section: Introductionmentioning
confidence: 99%
“…For BEV, various patient series have suggested an increase in diffusely or distantly recurring tumors [11,19]. This gliomatosis-like phenotype or remote spread is best depicted on fluid-attenuated inversion recovery (FLAIR) MRI sequences [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation